Severe cardiac AL amyloidosis in an elderly patient with multiple SARS-CoV-2 reinfection: a case report - E. V. Reznik; T.L. Nguyen; O. A. Ettinger; V. An. Lazarev; S. V. Borisovskaya; A. I. Guseva; A. V. Salikov; G. N. Golukhov (Российский кардиологический журнал)
Introduction. The relationship between systemic amyloidosis and coronavirus disease 2019 (COVID-19) has not been sufficiently studied to date. This paper presents a case of the persistence of COVID-19 markers in an elderly patient with systemic amyloidosis.Brief description. A 74-year-old patient with heart failure with preserved ejection fraction and type 2 diabetes was repeatedly hospitalized due to decompensated heart failure. Based on the data of protein electrophoresis with immunotyping, biopsy of subcutaneous fat and bone marrow, echocardiographic data, the patient was diagnosed with systemic AL amyloidosis with cardiac involvement. During hospitalizations in April, August and December 2020, positive polymerase chain reaction test for SARS-CoV-2 were obtained, while there were no clinical manifestations of infection for a long time and adequate antibody production.Conclusion. A case report demonstrates multiple SARS-CoV-2 reinfection in a severe comorbid elderly patient, as an unfavorable prognostic factor.